HAMBATAN FOLLOW-UP SKRINING DIABETES PADA IBU POSTPARTUM DENGAN RIWAYAT GESTATIONAL DIABETES MELLITUS: SCOPING REVIEW - Wardani, Suci Fitriana Pramudya; Fajarini, Nurbita (Jurnal Borneo Cendekia, 2023)
Women with a history of GDM are at increased risk of developing type 2 diabetes mellitus (T2DM). To prevent T2DM, postpartum women with a history of GDM should have regular diabetes screenings. However, the screening participation rate is still low for reasons that are not clear. This scoping review aims to identify barriers to follow-up diabetes screening in women with a history of GDM. Articles search was conducted through three databases (PubMed, ScienceDirect, and ProQuest) with the following inclusion criteria: English articles, published in the last 10 years, are original research, discussing obstacles related to follow-up diabetes screening in postpartum mothers with a history of GDM. Based on search results in three databases, 354 articles were identified. Seven articles were selected to be used in this scoping review, with a total sample size of 636 people. Barriers related to follow-up diabetes screening in postpartum mothers with a history of GDM that were often found were: being busy taking care of the baby, having an unpleasant experience with the OGTT test, fear of diagnosis and its consequences, lack of knowledge, having false beliefs about GDM, facilities, and inadequate infrastructure. To optimize this diabetes screening follow-up, efforts should be made to increase coordination, knowledge, and awareness among both women with a history of GDM and health care providers about the impact of GDM and the importance of follow-up diabetes screening.